Pengaruh Supervisi Kepala Sekolah dan Disiplin Kerja terhadap Kinerja Guru di SMP Negeri 6 Satap Fatuleu - Yorni Demus Hengki Nomleni (Institut Agama Hindu Negeri Tampung Penyang Palangkaraya, 2022)
The purpose of this study was to determine and analyze the effect of principal supervision on teacher performance, to determine and analyze the effect of work discipline on teacher performance and to jointly identify and analyze the effect of principal supervision and work discipline on teacher performance at SMP Negeri 6 Satap. Fatuleu. The method used in this study is a quantitative method with a sample of 30 teachers while the data collection techniques are observation, questionnaires and documentation with data analysis techniques using multiple linear regression analysis to determine the effect between variables. The findings of the research are 1) the effect of Principal Supervision (X1) on Teacher Performance (Y) has a significant and strong influence between these two variables with an f value of 0.686 > 0.05 with a Sig value. 0.414. 2). The influence of work discipline (X2) and Teacher Performance (Y) has a significant and strong relationship between these two variables with an f value of 145.267 > 0.05 with a Sig value. 0, 000. 3). Based on the comparison between the variables of Principal Supervision (X1) and Work Discipline (2) and Teacher Performance (Y) has a very strong influence, namely with a value of R2 = 0.838 in other words this relationship has an effect of = 83.8%. Conclusions 1) The influence of the principal's supervision on the performance of teachers at SMP Negeri 6 Satap Fatuleu has been implemented well. This means that Principal Supervision has a significant effect on improving teacher performance at SMP Negeri 6 Satap Fatuleu. 2) The effect of work discipline on teacher performance at SMP Negeri 6 Satap Fatuleu is going well. This means that work discipline has a significant effect on improving teacher performance at SMP Negeri 6 Satap Fatuleu. 3) The effect of principal supervision and work discipline on teacher performance at SMP Negeri 6 Satap Fatuleu simultaneously has a significant effect on improving teacher performance at SMP Negeri 6 Satap Fatuleu Barat.